Activity and release of enzymes embedded in polyvinyl alcohol-based cryohydrogels under –20 °C storage conditions - Naumenko, Yevheniia; Repina, Svitlana; Khala, Iryna; Manhasarov, Dmytro; Nardid, Oleg (Problems of Cryobiology and Cryomedicine, 2026)
Probl Cryobiol Cryomed. 2026; 36(1): 69—72